HALOGEN CONCENTRATIONS IN PORE WATERS AND SEDIMENTS OF THE NANKAI TROUGH, JAPAN: IMPLICATIONS FOR THE ORIGIN OF GAS HYDRATES - Muramatsu Y.; Doi T.; Tomaru H.; Fehn U.; Takeuchi R.; Matsumoto R. (My University, 2007)
Presented here are halogen concentrations (Cl, Br and I) in pore waters and sediments from three deep cores in gas hydrate fields of the Nankai Trough area. The three cores were drilled between 1999 and 2004 in different geologic regions of the northeastern Nankai Trough hydrate zone. Iodine concentrations in all three cores increase rapidly with depth from seawater concentrations (0.00043 mmol/L) to values of up to 0.45 mmol/L. The chemical form of I was identified as I-, in accordance with the anaerobic conditions in marine sediments below the SO4 reduction depth. The increase in I is accompanied by a parallel, although lesser increase in Br concentrations, while Cl concentrations are close to seawater values throughout most of the profiles. Large concentration fluctuations of the three halogens in pore waters were found close to the lower boundary of the hydrate stability zone, related to processes of formation and dissociation of hydrates in this zone. Generally low concentrations of I and Br in sediments and the lack of correlation between sediment and pore water profiles speak against derivation of I and Br from local sediments and suggest transport of halogen rich fluids into the gas hydrate fields. Differences in the concentration profiles between the three cores indicate that modes of transportation shifted from an essentially vertical pattern in a sedimentary basin location to more horizontal patterns in accretionary ridge settings. Because of the close association between organic material and I and the similarity of transport behavior for I- and CH4, the results suggest that the CH4 in the gas hydrates also was transported by aqueous fluids from older sediments into the present layers. © 2007 Elsevier Ltd. All rights reserved.